RETRACTED: A dynamic relationship between renewable energy consumption, non-renewable energy consumption, economic growth and CO2 emissions: Evidence from Asian emerging economies - Zhang, Taiming; Yin, Jiemin; Li, Zhenghao; Jin, Yitong; Ali, Arshad; Jiang, Bin (Frontiers in Environmental Science, 2023)
This study aims to explore the relationship between renewable energy consumption, non-renewable energy consumption, carbon dioxide emissions and economic growth in China, India, Bangladesh, Japan, South Korea and Singapore using panel Augmented Mean Group (AMG) estimation techniques over the period 1975–2020. The results of the analysis show that renewable energy consumption, non-renewable energy consumption, employed labor force, and capital formation contribute significantly to long-run economic growth. The study also found that non-renewable energy consumption significantly increased long-term carbon emissions, while renewable energy consumption significantly reduced long-term carbon emissions. GDP and GDP3 have a significant positive impact on environmental degradation, while GDP2 has a significant negative impact on environmental degradation, thereby validating the N-type EKC hypothesis in selected emerging economies. The countrywise AMG strategy records no EKC in India and Bangladesh, an inverted U-shaped EKC in China and Singapore, and an N-shaped EKC in Japan and South Korea. Empirical evidence from the Dumitrescue-Hurlin (2012) panel causality test shows that there is a two-way causality between renewable energy consumption and economic growth, supporting the feedback hypothesis. Strategically, empirical evidence suggests that higher renewable energy is a viable strategy for addressing energy security and reducing carbon emissions to protect the environment and promote future economic growth in selected Asian countries.